Preface of Proceedings of GNOME 2014 — Festschrift for Gaston Gonnet - Anisimova, Maria; Dessimoz, Christophe (PeerJ PrePrints, 2014)
It is an immense pleasure to present this Festschrift on the occasion of Professor Gaston H. Gonnet’s retirement. This volume accompanies the associated symposium Gonnet is Not Only about Molecular Evolution (GNOME) on the 4th of July 2014 at ETH Zurich. Born in Uruguay, Gaston completed his undergraduate studies in Montevideo before going to Waterloo, Canada, where he completed his Master’s and, just less than two years later, his PhD degree under the supervision of J. Alan George.
Keywords: Festschrift; GNOME2014; Preface